ESTIMATING THE GEOTECHNICAL PROPERTIES OF HETEROGENEOUS ROCK MASSES SUCH AS FLYSCH - Marinos P.; Hoek E. (My University, 2001)
The design of tunnels and slopes in heterogeneous rock masses such as flysch presents a major challenge to geologists and engineers. The complex structure of these materials, resulting from their depositional and tectonic history, means that they cannot easily be classified in terms of widely used rock mass classification systems. A methodology for estimating the Geological Strength Index and the rock mass properties for these geological formations is presented in this paper.
Keywords: ROCK MASS CLASSIFICATION; GSI; GEOTECHNICAL PROPERTIES; FLYSCH